The Influence of Personalized Marketing on Customer Engagement and Customer Lifetime Value - Atkhmad Fauzi Sayuti; Kiran Iqbal; Zainab Ali (Yayasan Adra Karima Hubbi, 2025)
Personalized marketing has emerged as a critical strategy for enhancing customer engagement and customer lifetime value (CLV) in today’s competitive business environment. By leveraging customer data and advanced analytics, businesses can deliver tailored experiences that resonate with individual preferences and behaviors. This study examines the influence of personalized marketing on customer engagement and CLV, focusing on its impact on customer satisfaction, loyalty, and long-term profitability. The research aims to identify effective strategies for implementing personalized marketing and propose recommendations for maximizing its impact on customer relationships. Using a mixed-methods approach, this study combines quantitative analysis of customer data with qualitative interviews with marketing professionals and customers. Data were analyzed to assess the relationship between personalized marketing, customer engagement, and CLV. The findings reveal that personalized marketing significantly enhances customer engagement, leading to higher satisfaction and loyalty. However, challenges such as data privacy concerns and implementation costs can hinder its effectiveness. The study concludes that businesses must balance personalization with ethical data practices to maximize the impact of personalized marketing on CLV. This research contributes to the discourse on marketing strategy by providing practical recommendations for businesses to enhance customer relationships and drive long-term profitability through personalized marketing.